2021
DOI: 10.1097/aln.0000000000003853
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Quadratus Lumborum Block Does Not Provide Superior Pain Control after Hip Arthroscopy: A Double-blinded Randomized Controlled Trial

Abstract: Background Hip arthroscopy is associated with moderate to severe postoperative pain. This prospective, randomized, double-blinded study investigates the clinically analgesic effect of anterior quadratus lumborum block with multimodal analgesia compared to multimodal analgesia alone. The authors hypothesized that an anterior quadratus lumborum block with multimodal analgesia would be superior for pain control. Methods Ninety-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 21 publications
5
41
1
Order By: Relevance
“…While most of the studies included in our review utilized the posterior QLB, a few did report the use of anterior or lateral QLB but with variable results. While Haskins et al (33) reported the lack of beneficial effect with anterior QLB in hip arthroscopic surgeries, Kukreja et al (26) found a statistically significant reduction in pain scores and opioid consumption with anterior QLB in patients undergoing hip arthroplasties. Another retrospective study of Kinjo et al (27) also reported no significant difference in pain scores with anterior QLB.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While most of the studies included in our review utilized the posterior QLB, a few did report the use of anterior or lateral QLB but with variable results. While Haskins et al (33) reported the lack of beneficial effect with anterior QLB in hip arthroscopic surgeries, Kukreja et al (26) found a statistically significant reduction in pain scores and opioid consumption with anterior QLB in patients undergoing hip arthroplasties. Another retrospective study of Kinjo et al (27) also reported no significant difference in pain scores with anterior QLB.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen articles were selected for full-text analysis. Of them, thirteen studies fulfilled the inclusion criteria and were analyzed in this review (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Details Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations